Microbial Deconstruction Of Cellulosic Cotton Fabric: Isolation, Identification And Morphological Confirmation Of Fungal Biodegradation - Bhavini I. Surati; Dr. Farida P. Minocheherhomji (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2025)
The present investigation focuses on the isolation, identification, and confirmation of fungal degradation of cotton fabric under humid storage conditions. Degraded cotton samples were collected from textile units in Jaipur and Surat and screened for fungal contamination using Sabouraud Dextrose Broth. Five dominant fungal strains were isolated—Aspergillus flavus, Lichtheimia ramosa, Penicillium oxalicum, Aspergillus nidulans, and Aspergillus niger. Cellulolytic activity was evaluated through qualitative and quantitative assays, including CMC agar plate, DNSA, and filter paper assays. The relative cellulase activity, measured by optical density at 540 nm, indicated significant reducing sugar release, with A. flavus exhibiting the highest activity. SEM analysis confirmed structural damage to cotton fibers post fungal exposure, correlating with enzyme-mediated cellulose hydrolysis. This study demonstrates the biodegradative potential of fungal species in humid textile environments, contributing to an improved understanding of microbial deterioration of cotton-based materials.